An Exploratory Study of Innovative Training, Experiences, and Perceived Teaching Competencies in Pre-Service Physics Teacher Education - Novinta Nurulsari; Charyna Ayu Rizkyanti; Risa Haridza; Fadiyah Farah Khoirunnisa (Jurnal Materi dan Pembelajaran Fisika, 2025)
This study explores how preservice physics teachers (PPTs) confront and respond to challenges in developing core teaching competencies amid the demands of 21st-century education. It aims to understand the interrelationship between innovative training, professional experience, and essential teaching competencies that shape teacher readiness.Using a qualitative case study design, the research captures authentic experiences from ten PPTs at a public university in Indonesia, purposively selected to represent variations in prior teaching experience and exposure to creative training programs. Data were collected through semi-structured interviews that encouraged participants to share narratives of professional growth, teaching challenges, and the use of innovative physics teaching strategies. Interview transcripts were analyzed using Quirkos 3.0 through an iterative coding process and thematic analysis, with credibility ensured through member checking and peer debriefing.The findings reveal three key insights: (1) innovative training provides a strong foundation for professional development and fosters student-centered learning environments; (2) field experiences expose participants to classroom realities such as diverse student backgrounds and difficulties in simplifying abstract physics concepts; and (3) essential competencies, including empathy, creativity, classroom management, and strong subject knowledge, emerge as crucial for effective teaching practice.Overall, the study demonstrates that preservice physics teacher education benefits from a cohesive and reflective approach that strengthens adaptive teaching skills, supports the formation of a strong professional identity, and enhances the quality of science teaching. The novelty of this study lies in mapping the interconnections between innovative training, field experience, and professional competencies of preservice physics teachers within the contextual framework of teacher education.